The association between substance use and depressive symptomatology in nursing university students in Mexico. (March 2019) - Tiburcio Sainz, Marcela; Nagy, Gabriela; Rosete Mohedano, Guadalupe; Martínez Vélez, Nora; Carreño García, Silvia; Pérez Cisneros, Daniel; Natera Rey, Guillermina
Abstract: The present study represents an ex post facto non-experimental study of undergraduate nursing students ( N = 1, 176) residing in Mexico whereby we examined the association between substance use and depressive symptomatology. The sample was composed primarily of women (70.1%), between the ages of 18 and 23 years (89.5%). Outcomes suggest a significant association between current clinically relevant depressive symptomatology 3-month marijuana, alcohol, and sedative use. Additionally, current depressive symptomatology was significantly associated with lifetime alcohol and sedative use. Lastly, current depressive symptomatology was significantly associated with both moderate/high risk level due to alcohol and sedative use. The present study is innovative as it examines possible associations between depressive symptomatology and 10 classes of substances concurrently for a group that is largely understudied, further contributing to the international literature in this area. Findings are discussed with regards to study limitations. Highlights: Nursing students who use sedatives are a greater risk of depressive symptomatology and clinical depression. Access to sedatives is part of the formative activities which might increase their vulnerability to substance use. Nursing students who use substances – namely sedatives, alcohol, and marijuana – may be at higher risk for depression. Substance use by nurses can impact their ability to adequately provide quality health services to others. Screening and brief intervention are a feasible option to reduce the risk of substance use problems among nursing students.